IDENTIFIKASI HASIL MAKROSKOPIS DAN MIKROSKOPIS URIN PADA PASIEN TUBERKULOSIS - Setyo Dwi Santoso; Christina Destri Wiwis Wijayanti; regina Linesiana (Jurnal SainHealth, 2022)
Tuberculosis (TB) is an infectious disease directly transmitted through the air. This disease is caused by the bacterium Mycobacterium tuberculosis. Tuberculosis requires an incubation period of 3-6 months from initial exposure to the bacteria. Patients identified with tuberculosis will be given anti-tuberculosis drugs intensively for 6 months. Long treatment time resulting in drug accumulation can affect the kidneys. Microscopic examination or urine sediment aims to detect kidney and urinary tract abnormalities and monitor the results of treatment. This study used an experimental research type, then the primary data were analyzed descriptively. Identification of the results of macroscopic and microscopic urine in tuberculosis patients in the hospital. Lungs Surabaya, showed the largest percentage of 75% macroscopic results of clear yellow urine. Microscopic results showed normal values compared to normal macroscopic and microscopic ranges of urine.Keywords :Tuberkulosis, Mikroskopis Urin, Makroskopis Urin